Dietary supplements for treatment of endometriosis: A review - Yalçın Bahat, Pınar; Ayhan, Işıl; Üreyen Özdemir, Eda; İnceboz, Ümit and Oral, Engin (Acta Biomedica Atenei Parmensis, 2022)
As search for optimal therapy continues for endometriosis, aid of dietary supplements is gaining attention. Supplements can be used for their anti-inflammatory, anti-oxidant, anti-proliferative and immune modulatory charactheristics. We reviewed the literature, evaluated and synthesized effects of vitamin D, zinc, magnesium, omega 3, propolis, quercetin, curcumin, N-acetylcysteine, probiotics, resveratrol, alpha lipoic acid, vitamin C, vitamin E, selenium and epigallocatechin-3-gallate. Based on results of in vitro, animal and human studies, it might be safe to say that dietary supplements can be used as a complementary treatment for endometriosis.